Characterization of β-Cyclodextrin Complexes with Natural Dye - Mimi Sakinah, A. M.; Norasiha, Hamid; Rohaida, Che Man (2009)
Natural dye was successfully solubilised in aqueous solution in forming inclusion complex with Î²-cyclodextrin (Î²-CD). To investigate molecular association, phase solubility studies were undertaken. In the presence of cyclodextrin, fluorescence absorbances were enhanced. Solid state inclusion complex was also prepared using co-precipitation method. The solid was characterized using Fourier Transform Infrared (FTIR) and X-ray Diffractometer (XRD). Using FTIR, the host-interaction have been evidenced by monitoring the changes in some guest molecule band relative to those observed in the spectra of the 1:1 physical mixtures and complex. XRD can give the order of structure in the solid inclusion. All the data from FTIR and X-Ray studies showed that it is possible to obtain an inclusion complex (1:1) in solid state.